The use of intravenous iron in pregnancy: for whom and when? A survey of Australian and New Zealand obstetricians - Sarah Smith-Wade; Giselle Kidson-Gerber; Antonia Shand; Luke Grzeskowiak; Amanda Henry (BMC, 2020)
Abstract Background Iron deficiency anaemia in pregnancy (IDAP) affects 11-18% of Australian pregnancies and is associated with adverse perinatal outcomes. National prescribing data suggests the use of intravenous iron in pregnancy is increasingly common. This study aimed to: 1) Establish the current patterns of intravenous iron use by Fellows of the Royal Australian and New Zealand College of Obstetricians (FRANZCOG) when treating iron deficiency and IDAP including immediately postpartum and; 2) Assess FRANZCOG opinions regarding potential trial of intravenous iron for first-line treatment of IDAP. Methods An online survey of RANZCOG Fellows practicing obstetrics was distributed in September 2018. Results were analysed descriptively and responses compared by clinician demographics using Chi-squared testing. Results Of 484 respondents (21% of FRANZCOG), 457 were currently practicing obstetrics. Most prescribed intravenous iron in pregnancy (96%) and/or postpartum (85%). Most intravenous iron was prescribed for IDAP (98%) rather than iron deficiency without anaemia (53%), and for IDAP most commonly second-line to failed oral iron supplementation and first-line in special circumstances (59%). Intravenous iron prescribing was associated with shorter time since FRANZCOG completion (p = 0.01), public hospital practice (p = 0.008) and higher hospital birth numbers (p = 0.01). Most respondents (90%) would consider a randomised controlled trial of first-line intravenous iron for IDAP, although views on appropriate thresholds differed. Conclusions Almost all respondents prescribed intravenous iron for IDAP, and while mostly used for second-line treatment over half sometimes used it first-line. With accelerating intravenous iron use, further research is required into its optimal use in pregnancy, recognizing important clinical outcomes and cost effectiveness.